Ocena podmiotu gospodarczego a możliwość uzyskania gwarancji ubezpieczeniowej - Dankiewicz, Robert (Assessment of Enterprise Vs. Possibility of Getting Insurance Guarantee, 2006)
In the paper the characteristics of the assessment criterion of enterprises interested in getting a guarantee was described. The problems within this issue were discussed. At the same time the necessity of applying the solutions was shown. The consequences from the guarator (insurer) were featured in case when they give up some of the areas of the assessment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 401-408